An Assessment Of Participatory Integrated Watershed Management In The Hilkot Watershed, Mansehra,Pakistan - Shah, Hakim (2008)
The 1600 ha Mountainous Hilkot Watershed, located in the Mansehra District, Pakistan had to support a population of 9500 people for their livelihood. Situated in moist temperate zone, the community is mostly dependent on agriculture, forestry, livestock and remittances for their livelihood. Due to ever increasing population, overgrazing, illicit cutting of forests for timber and fuel wood, lack of fuel wood alternatives, unawareness and extreme poverty, the natural resources are under tremendous pressure. A number of projects have been executed in the past in Hilkot watershed related to watershed management and natural resource management. The site was selected for the study due to the participatory watershed management program implemented in the area. This study was conducted to assess the impacts of participatory integrated watershed management in sustainable management and development of degraded natural resources of Hilkot watershed particularly with respect to People and Resource Dynamic Project (PARDYP) specifically on the contribution in the livelihood improvement and socio-economic development of the communities of the watershed. A cluster random sampling technique was used for the selection of sample size with sampling intensity of 20 percent. Out of 938 households, 188 (20%) were randomly selected and interviewed using a structured questionnaire while secondary information were collected from the local and national agencies. The assessment of the study indicates that the participatory integrated watershed management program in Hilkot watershed brought social, economic, institutional improvements and watershed development which led to increase in productivity and livelihood of people. The major social improvements were positive changes in the peoples’ attitudes and awareness, high community participation, capacity building and skill enhancement of households, improvement in women role and linkages among stakeholders and coordination among governmental and non – governmental agencies. The linkages and mutual cooperation among the stockholders, supported activities well which often resulted in more interaction among them as reported by 83% respondents. Although inhabited by different ethnic groups with divergent interests and political affiliation, conflicts were mostly resolved through mediation (67%), consultation (50%) and compensation (27%). In terms of mediation, the elder Jirga system was found to be the most influential way for resolution of disputes (83.5%).The study suggests that there was highest participation of male (87%) and female (70%) in the watershed activities. About 78% of the respondents participated in planning, 73% in monitoring and 56% in evaluation. There was also good participation in other activities viz. individual and monthly meetings (83%), trainings (65%), farmers’ days (67%) and income generating training (49%). Among the residents, the majority felt that there was increase in gender participation (69%), increase in decision making role (55%), increase in empowerment (47%), improvement in socio-economic level (56%) and improvement in overall condition of women (58.5%). There was high application of the techniques such as land preparation (51%), nursery raising (63%), cutting & budding (51%) as well as income generating trainings like food technology (31%), honeybee (46%), kitchen gardening (53%), sewing and embroidery (60%), which led to better productivity. The economic improvements brought by the watershed program, as stated by villagers include increase in agricultural and forestry activities, crop yields, employment opportunities and increase in household’s income, The overall natural management activities improved. A large number of the respondents reported increase in crop production (93%), number of trees planted (89%) and vegetable production (70%). The plantations especially of the fast growing tree species helped the locals to overcome their short term timber and fuel-wood requirements. The study suggests that wheat production increased from 1339 to 3275 kg/ha and rice from 1400 to 2950 kg/ha. In addition, with the introduction of the System of Rice Intensification (SRI) technique, the production of rice increased to 6650 kg/ha and a two fold increase in straw. The watershed activities were good sources of employment for the people of Hilkot particularly for the landless and small farmers. Poor farmers stopped migration to other areas for employment as income of households was increased due to watershed management activities as reported by majority of respondents (61.7%) to RS. 5000 in 2007 compared to RS. 2250 in 2002 due to improved varieties of cereal crops and skilled enhancement activities. Interestingly, majority of the respondents (98%) reported that the watershed program was helpful in raising household income and livelihood improvement. The watershed management impacts are the rehabilitation of degraded sites, improvements in field techniques, increase in water supply and reduction in soil erosion, the severe problems in Hilkot, which were addressed through adoption of several bio-engineering and vegetative rehabilitative measures reported by 81% respondents with increase in cereal crop production, vegetable and tree cover and improvement in drinking water. The overall assessment can be concluded that the participatory integrated watershed management program implemented in Hilkot watershed was successful in bringing social, economic, institutional and watershed management improvements in Hilkot watershed and increased the productivity and livelihood of communities. This approach could also be replicated in other watersheds especially in northern-Pakistan where the watershed conditions are similar to Hilkot.